2019
DOI: 10.2147/ijn.s206210
|View full text |Cite
|
Sign up to set email alerts
|

<p>Chimeric hepatitis B virus core particles displaying Neisserial surface protein A confer protection against virulent <em>Neisseria meningitidis</em> serogroup B in BALB/c mice</p>

Abstract: Purpose The primary goal of the present study was to explore and evaluate the highly conserved Neisserial surface protein A (NspA) molecule, fused with truncated HBV virus-like particles (VLPs), as a candidate vaccine against the virulent Neisseria meningitidis serogroup B (NMB). Methods NspA was inserted into the major immunodominant region of the truncated hepatitis B virus core protein (HBc; amino acids 1–144). The chimeric protein, HBc-N14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
4
4
0
Order By: Relevance
“…According to the results, the adjuvant positively affected the immune response in terms of IgG antibodies. Consistent with these results, Hou et al (2019) reported that the maximum antibody titer was produced when the HBc-fused antigen was injected with Freund's adjuvant. In spite of the self-adjuvant property of the VLP vaccine, the utilization of proper adjuvant can strongly elevate the e cient immune response [15,39,40].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…According to the results, the adjuvant positively affected the immune response in terms of IgG antibodies. Consistent with these results, Hou et al (2019) reported that the maximum antibody titer was produced when the HBc-fused antigen was injected with Freund's adjuvant. In spite of the self-adjuvant property of the VLP vaccine, the utilization of proper adjuvant can strongly elevate the e cient immune response [15,39,40].…”
Section: Discussionsupporting
confidence: 68%
“…Consistent with these results, Hou et al (2019) reported that the maximum antibody titer was produced when the HBc-fused antigen was injected with Freund's adjuvant. In spite of the self-adjuvant property of the VLP vaccine, the utilization of proper adjuvant can strongly elevate the e cient immune response [15,39,40]. Although Freund's adjuvant might not be safe for humans, because it is reported to be more highly immunogenic than other adjuvants in mice [41,42], we preferably used this adjuvant to examine the general response of HBc-E VLP in the presence to a potent adjuvant in comparison with immunized mice that were solely injected by HBc-E VLP.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…According to the results, the adjuvant positively affected the immune response in terms of IgG antibodies at four weeks. Consistent with these results, [ 13 ] reported that the maximum antibody titer was produced when the HBc-fused antigen was injected with Freund’s adjuvant. In spite of the self-adjuvant property of the VLP vaccine, the utilization of proper adjuvant can strongly elevate the efficient immune response [ 13 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 65%
“…Their 180 subunits are structured in icosahedral T3 geometry with a diameter ranging from 25-30nm [36][37][38][39][40][41][42]. The last VLP tested was the hepatitis B virus protein capsid HBcAg which with 34 nm of diameter and 240 subunits was the largest VLP tested [22,[43][44][45]. Recently, the successful use of HBcAg as a scaffold for the display through genetic fusion of two meningococcal antigens (fHbp and NadA) has been reported.…”
Section: Introductionmentioning
confidence: 99%